2019
DOI: 10.1002/chem.201901000
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of Azolium Tetraphenylborate with Isopropylthioxanthone: A New Class of N‐Heterocyclic Carbene (NHC) Photogenerator for Polyurethane, Polyester, and ROMP Polymers Synthesis

Abstract: In the search of smarter routes to control the conditions of N‐heterocyclic carbene (NHCs) formation, a two‐component air‐stable NHC photogenerating system is reported. It relies on the irradiation at 365 nm of a mixture of 2‐isopropylthioxanthone (ITX) with 1,3‐bis(mesityl)imidazoli(ni)um tetraphenylborate. The photoinduced liberation of NHC is evidenced by reaction with a mesitoyl radical to form an NHC‐radical adduct detectable by electron spin resonance spectroscopy. The NHC yield can be determined by 1H N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Ph 2 BOH was found to react with the photogenerated IMes to give an IMes-Ph 2 BOH ate-complex. While it is difficult to avoid the formation of NHC-boron adduct, our recent investigation showed that such complex did not prevent the activity of its NHC photogenerator in ringopening methathesis polymerization or for synthesis of polyurethane, 22 but could have a detrimental effect on other reactions. Knowledge about the precise photochemical mechanism offers now the possibility for improving the photoinitiating system in a rational way, and create a new generation of NHC photogenerator.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Ph 2 BOH was found to react with the photogenerated IMes to give an IMes-Ph 2 BOH ate-complex. While it is difficult to avoid the formation of NHC-boron adduct, our recent investigation showed that such complex did not prevent the activity of its NHC photogenerator in ringopening methathesis polymerization or for synthesis of polyurethane, 22 but could have a detrimental effect on other reactions. Knowledge about the precise photochemical mechanism offers now the possibility for improving the photoinitiating system in a rational way, and create a new generation of NHC photogenerator.…”
Section: Discussionmentioning
confidence: 92%
“…-(E ox = 0.94 eV). 22 It also highlights a more complex mechanism where photogenerated NHC can also interact with triplet ITX and compete with BPh 4 for charge transfer.…”
Section: Assignment Of Transient Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative conversion of IMes into IMes-carbodiimide (CDI) adduct was described elsewhere. 29 The irradiation sources include a medium pressure Xe-Hg lamp (75 mW cm À2 , Hamamatsu, LC-9588/01A), a LED@365 nm (65 mW cm À2 , Hammamatsu LC-L1V3) and a LED@405 nm (100 mW cm À2 , Thorlabs M405L2). The irradiances were determined by using an optical power meter PM100D from Thorlabs.…”
Section: Syntheses and Proceduresmentioning
confidence: 99%
“…22 Recently, we replaced the PAG with a NHC photogenerator and used a stable, commercially available dimeric Ru(II) complex as metathesis inactive catalyst (Scheme 1). 28,29 Our tandem system made up of 1,3-bis(mesityl)imidazolium tetraphenylborate IMesH + BPh 4 À (1) as NHC progenitor and [RuCl 2 (p-cymene)] 2 precatalyst (Ru-1) proved to be very efficient at ROMP of NB. In comparison with the examples discussed above, a safer UVA radiation (320-400 nm) was employed, and no ligand displacement occurred.…”
Section: Introductionmentioning
confidence: 99%